THE SWELLING OF EXPANSIVE SUBGRADE AT WATES-PURWOREJO ROADWAY STA. 8 127 - Agus Setyo Muntohar (Institute of Research and Community Outreach - Petra Christian University, 2006)
Damage of structures and road beds due to expansive soil are common in Indonesia. One example is the deterioration of a road section at Sta. 8 + 127 of the Purworejo-Wates Highway. This Technical Note presents the investigation of the cause of the deterioration of the road bed. The author concludes that the sub grade is an expansive soil and the swelling pressure is able to lift the overlaying pavement and cause considerable cracking. Abstract in Bahasa Indonesia : Kerusakan struktur bangunan dan perkerasan jalan karena tanah ekspansif merupakan masalah yang banyak terjadi di Indonesia. Salah satu kerusakan perkerasan jalan yang terjadi karena tanah ekspansif adalah kerusakan perkerasan jalan di Sta. 8+127, Jalan Raya Purworejo-Wates. Technical Note ini menyajikan penyelidikan penyebab kerusakan perkerasan jalan tersebut. Penulis menyimpulkan bahwa tanah dasar di lokasi tersebut adalah tanah ekspansif dengan tekanan mengembang yang sanggup merusak struktur perkerasan jalan di atasnya.